Ensamblaje de insectos con actividad nocturna en dos arrozales de los Llanos Noroccidentales de Venezuela - Azofeifa Romero, Yara (2020)
In order to contribute to our knowledge on assemblages of nocturnal insects associated with rice crops in Venezuela, two rice fields located in Acarigua and Turén, Portuguesa State, were studied. Sampling was carried out between November 2013 and October 2014, covering two consecutive cultivation cycles (rainy and dry season). Insects were collected with an intersection trap with white light during each phase of the rice’s life cycle (vegetative, reproductive and ripening). Taxonomic identification was performed at family level, with assignment of morphospecies. A total of 110.878 insects in 98 morphospecies were collected, of which 72% were common in both locations. The most abundant families were Scarabaeidae, Hydrophilidae, Heteroceridae, Veliidae and Staphylinidae. In addition, the following pest species of rice were recorded: Hortensia similis, Tagosodes orizicolus, Trigonotylus sp., Oebalus sp., Lissorhoptrus sp., Rupela albinella and Spodoptera frugiperda. Abundance, richness and diversity were higher during the rainy season. Regarding growth stage of rice plants, abundance and diversity were higher during ripening stage, whereas species richness was higher during the vegetative stage. In addition, an abundance ratio of approximately 1:1 between predators and phytophagous insects was observed during the three growth stages of rice life cycle. These results suggest: (1) insects diversity could respond positively to rainfall conditions and abundance of high quality food resources and (2) high abundance of predatory insects could be associated with presence of abundant phytophagous populations.